Let's analyze the given Java code to determine its output:
Code:
public static void main(String[] args) {
int a = 5;
a++;
System.out.println(a);
a -= (a--) - (--a);
System.out.println(a);
}
Explanation:
-
Initial Code Analysis:
- int a = 5;
initializes a
with the value 5
.
- a++;
increments a
by 1
. After this operation, a
becomes 6
.
- System.out.println(a);
prints the value of a
, which is 6.
-
Second Part of the Code:
- a--
is the post-decrement operator. It returns the value of a
before decrementing it. So, a--
evaluates to 6
, and then a
is decremented to 5
.
- --a
is the pre-decrement operator. It decrements a
first, so --a
evaluates to 4
, and a
becomes 4
.
- Therefore, the expression a -= (a--) - (--a)
translates to a -= 6 - 4
:
6 - 4
evaluates to 2
.
- Thus,
a -= 2
is equivalent to a = a - 2
. Since a
is 4
at this point, this becomes 4 - 2
, which results in 2
.
- System.out.println(a);
prints the value of a
, which is 4.
Conclusion:
The output of the program is:
- 6 (after the
a++
operation)
- 4 (after the
a -= (a--) - (--a)
operation)